Частотный анализ речи погибших 11 сентября 2001 года. На материале звонков людей, заключенных в башнях - Мазун, М.Д. (Культура народов Причерноморья, 2014)
В данной статье рассмотрены проблемы эмоциональных переживаний, которые входят в
психоэмоциональную область сознания человека и являются весомыми компонентами его
существования, поведения, контакта с внешним миром и другими людьми. Эмоции и чувства – это
своеобразная реакция организма на ситуации и события, которые происходят в жизни. Эмоциональная
сфера человека была предметом глубокого и детального анализа представителями разных наук. В
первую очередь, психологов, философов и, конечно же, лингвистов. Обобщая, можно сказать, что
частотный анализ предполагает, частоту появления заданной буквы алфавита достаточно длинных
разных текстов одного языка. Емоційні переживання входять в психоемоційну область свідомості людини і є вагомими
компонентами її існування, поведінки, контакту із зовнішнім світом і іншими людьми. Емоції та
почуття - це своєрідна реакція організму на ситуації та події, які відбуваються в житті. Емоційна
сфера людини була предметом глибокого і детального аналізу представниками різних наук. У першу
чергу психологів, філософів і, звичайно ж, лінгвістів. Узагальнюючи, можна сказати, що частотний
аналіз передбачає, частоту появи заданої букви алфавіту досить довгих різних текстів однієї мови. Emotional experiences are included in the psycho-emotional area of human consciousness and are
strong components of its existence, behavior, contact with the outside world and other people. Emotions and
feelings - are this kind of reaction to situations and events that occur in life. Emotional sphere of human has
been the subject of deep and detailed analysis of representatives of different sciences: psychologists,
philosophers, linguists. Summarizing, we can say that the frequency analysis suggests the frequency of a given
letter of the alphabet long enough different texts one language. September 11, 2001, thousands of people trapped
in the twin towers of the World Trade Center trying to get through to the outside world. Many of them knew that
time was short; they tried to talk with loved ones for the last time, while others tried to call emergency services,
for what to know what is happening and to find an escape route. Fear, bordering on panic, rescue attempt, mass
and individual panic attacks, often nearer the hour of death of prisoners in the towers of people allowed to
analyze the psycho-emotional state of a person at critical moments. Material analysis began recording
conversations and messages on answering machines, killed in the last minutes and hours of their lives.